1980
DOI: 10.3109/00016348009155398
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Fetal Heart Rate Patterns with Umbilical Artery pH and Catecholamines During Last Hour of Labor

Abstract: Fetal heart rate (FHR) patterns were analysed during last hour of labour and correlated to umbilical artery pH and catecholamine (CA) levels. Fetuses with pathological FHR had significantly higher levels of CA than those with normal FHR. Particulary high levels were found in fetuses with bradycardia and late decelerations. FHR was further analysed by a computer (DPAC, data processor and computer) in 100 women during last hour of labor. No correlation between deceleration areas of variability and umbilical arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

1982
1982
1992
1992

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
4
9
0
Order By: Relevance
“…There was a significant inverse relation with NE concentrations rising as tcpO 2 values decreased. No correlation could be detected between arterial E levels and the tcpO 2 .…”
Section: Catecholamine Concentrations In Arterial Andmentioning
confidence: 80%
See 4 more Smart Citations
“…There was a significant inverse relation with NE concentrations rising as tcpO 2 values decreased. No correlation could be detected between arterial E levels and the tcpO 2 .…”
Section: Catecholamine Concentrations In Arterial Andmentioning
confidence: 80%
“…Various investigators have by HUGH [14] for intrapartum fetal monitoring reported that analogous correlations exist between are contradictory. Some authors reported good catecholamines, acid-base balance [2,10,18,20], agreement between fetal arterial and transand the APGAR score [18,25]. The results on cutaneous pO 2 levels [11].…”
Section: Catecholamine Extraction By the Placentamentioning
confidence: 99%
See 3 more Smart Citations